National cyber security strategies for digital economy - Teoh, C.S. (IEEE Computer Society, 2017)
Digital economy is strengthening in prominence and relevance in the era of digital transformation. The economic opportunity and growth of nations are dependent on the digital world, as world community increasingly connected in the cyberspace. The boom in digital economy is coupled with cyber risks and cyber threats for nations. National cybersecurity strategy (NCSS) is an essential element as cybersecurity is needed to protect and enable digital economy. This article seeks to gain insights on the correlation of the development of the NCSS and the success of digital economy of the nation. NCSS of nine nations analysed based on digital economy success. The top nation of digital economy released its NCSS the latest, in 2016. NCSS is not a requirement to kick start digital economy. It is, however, essential for the continuous growth and success in digital economy. © 2017 IEEE.